2018
DOI: 10.1002/bdd.2117
|View full text |Cite
|
Sign up to set email alerts
|

Human UGT2B7 is the major isoform responsible for the glucuronidation of clopidogrel carboxylate

Abstract: Clopidogrel is predominantly hydrolyzed to clopidogrel carboxylic acid (CCA) by carboxylesterase 1, and subsequently CCA is glucuronidated to clopidogrel acyl glucuronide (CAG) by uridine diphosphate-glucuronosyltransferases (UGTs); however, the UGT isoenzymes glucuronidating CCA remain unidentified to date. In this study, the glucuronidation of CCA was screened with pooled human liver microsomes (HLMs) and 7 human recombinant UGT (rUGT) isoforms. Results indicated that rUGT2B7 exhibited the highest catalytica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
(82 reference statements)
0
8
0
Order By: Relevance
“…In summary, we characterized UGT2B17 in first-pass effect organs, whose role in drug metabolism remains understudied and underappreciated. For example, while one study showed UGT2B17 to be one of the main isoforms responsible for clopidogrel acyl glucuronide (CAG) formation [47], another study did not include this isoform and hence concluded that UGT2B7 forms CAG [48]. In addition, TRT has recently come under scrutiny due to reports of possible increased cardiovascular events, and the risks and benefits of TRT still remain contentious among practitioners [14,4951].…”
Section: Discussionmentioning
confidence: 99%
“…In summary, we characterized UGT2B17 in first-pass effect organs, whose role in drug metabolism remains understudied and underappreciated. For example, while one study showed UGT2B17 to be one of the main isoforms responsible for clopidogrel acyl glucuronide (CAG) formation [47], another study did not include this isoform and hence concluded that UGT2B7 forms CAG [48]. In addition, TRT has recently come under scrutiny due to reports of possible increased cardiovascular events, and the risks and benefits of TRT still remain contentious among practitioners [14,4951].…”
Section: Discussionmentioning
confidence: 99%
“…About 90% of clopidogrel is hydrolyzed by the polymorphic carboxylesterase 1 (CES1) to a pharmacologically inactive carboxylic acid metabolite, [13][14][15] which is further glucuronized to an acyl-b-D-glucuronide metabolite by uridine 5 0 -diphospho-glucuronosyltransferase (UGT) 2B enzymes. 16,17 The bioactivation of clopidogrel to the pharmacologically active cis-5-thiol metabolite is susceptible to changes in CYP2C19 activity, 18,19 but also CYP3A contributes to clopidogrel activation. For example, grapefruit juice, an inhibitor of CYP3A4 in the gut wall, has impaired the bioactivation of clopidogrel and consequently the inhibition of platelet aggregation.…”
Section: What Does This Study Add To Our Knowledge?mentioning
confidence: 99%
“…Clopidogrel is a prodrug, activated in two steps. About 90% of clopidogrel is hydrolyzed by the polymorphic carboxylesterase 1 (CES1) to a pharmacologically inactive carboxylic acid metabolite, which is further glucuronized to an acyl‐ β ‐D‐glucuronide metabolite by uridine 5′‐diphospho‐glucuronosyltransferase (UGT) 2B enzymes . The bioactivation of clopidogrel to the pharmacologically active cis ‐5‐thiol metabolite is susceptible to changes in CYP2C19 activity, but also CYP3A contributes to clopidogrel activation.…”
mentioning
confidence: 99%
“…CLP-C Is Not an Mrp3 Substrate. Although it is an intermediate metabolite of clopidogrel, CLP-C is glucuronidated to CLP-G principally by UGT2B7 (Ji et al, 2018). In this study, the liver-to-plasma ratio of CLP-C in Abcc3 KO mice was approximately 37% of that in WT mice (Fig.…”
Section: Resultsmentioning
confidence: 52%